A study of factors that affecting performance of Islamic banks in Malaysia: Analysis based on camel framework / Norfaraahanin Mohd Salleh - Mohd Salleh, Norfaraahanin (Faculty of Business Management, 2017)
Capital adequacy, Asset quality, Management competency, Earning quality, and Liquidity, or known as the CAMEL framework is one of the famous method used by researchers to evaluate the performance of the banks. Therefore these paper focus to identify relationship and which variables on the CAMEL framework affect the performance of the Islamic bank in Malaysia the most. Based on Panel Regression Random Effect, its turn out that AQ is the one that give more effect on the performance of the bank followed by CA and MC. The outcome of this study is important to financial institutions and policymaker such as Bank Negara Malaysia (BNM) and Security Commissions (SC) in creating a new policy that will enhance the future banking system in Malaysia.